Cover Image, Volume 90, Number 6, June 2018. Issue 6 (6th April 2018) - NikNadia, NMN; Tan, Chee Wah; Ong, Kien Chai; Sam, I‐Ching; Chan, Yoke Fun
Abstract : The cover image, by NMN NikNadia et al., is based on the Short Communication Identification and characterization of neutralization epitopes at VP2 and VP1 of enterovirus A71, DOI:10.1002/jmv.25061 .